2010
DOI: 10.1007/s00289-010-0408-5
|View full text |Cite
|
Sign up to set email alerts
|

Polycarbonate reinforced with silica nanoparticles

Abstract: Nanocomposites of polycarbonate (PC) reinforced with nanosized silica particles were prepared by a melt mixing technique in an internal mixer. Two kinds of commercial hydrophilic fumed silicas differing in their specific surface area were added in amounts up to 5% by volume, and their reinforcing action was compared to that of organically modified silica, loaded in the same amounts. Particle–matrix interactions were investigated by means of rheological and dynamic-mechanical thermal analysis, demonstrating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…This was related to the reduced particle-particle interactions dominated by hydrogen bonding ensued from the hydroxide groups on the silica surface and the carbonyl groups in the PC [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…This was related to the reduced particle-particle interactions dominated by hydrogen bonding ensued from the hydroxide groups on the silica surface and the carbonyl groups in the PC [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the addition of 10 wt% EPC has caused a decline in E′ of the PC; it was further improved by the addition of small amount of SiO 2 NPs. The similar trend for increasing the E ′ was observed by compounding SiO 2 NPs with the PC . In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the composite has paramagnetic properties after adding ferrite nanoparticles to the polymer matrix: high concentrations of CoFe 2 O 4 improve the magnetic properties of the composite. PC/nanosilica (SiO 2 ) nanocomposites were prepared by a melt-blending technique (Biswal et al, 2013;Luyt et al, 2011). The behavior, however, is not linear, with the largest increases; 16% of Young's modulus and 20% of hardness were achieved on samples containing 2 wt% magnetic nanofiller.…”
Section: Polycarbonates and Nanooxides Nanocompositesmentioning
confidence: 99%
“…The behavior, however, is not linear, with the largest increases; 16% of Young's modulus and 20% of hardness were achieved on samples containing 2 wt% magnetic nanofiller. Using nanosilica as a filler in PC nanocomposite, it is possible to increase the thermal stability and viscosity of the nanocomposites with respect to the pristine matrix (Luyt et al, 2011). Montaung et al (2013) prepared PC nanocomposites by melt compounding with different amounts of ZrO 2 , 1-5 wt%, and found that the amount of ZrO 2 influences the thermal degradation process.…”
Section: Polycarbonates and Nanooxides Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation